How to improve the service concept in the microfinance organization: credit union Althea - Manuzina, Yulia (HAAGA-HELIA ammattikorkeakoulu, 2013)
Over the past 20 years microfinance in Russia has developed widely. Nowadays this market faces tremendous changes as comptetion inside this sector is growing rapidly. Credit unions have been the pioners in this field recognized among consumers and currently they take thier own niche as microfinance providers. However, due to strong competition and legislative challanges, credit unions have to explore new approaches to service delivery and customer communication. This research focused on the operation of credit union Althea located in Petrozavodsk, the Republic of Karelia, Russia. The purpose of the study was to improve the current service concept in the credit union by offering new ways in service delivery. As there is a lack of youth in the membership base of credit union Althea, the research targeted young people at the age 25-35 years old that live permanently in Petrozavodsk. The research was designed by using qualitative and quantitative methods. Qualitative methods were utilized while performing the blueprint analysis of the company’s loan issuing operation. The survey among the youth was conducted by means of quantitative methods in a form of a structured questionnaire. The reaserch timeframe was December 2012-May 2013. The result of the reseach showed that there is still a lack of information about the credit union among the youth of Petrozavodsk. Hence, young people do not trust the organization. From the technological point of view, the procedure of borrowing is still complex and unflexible, there is a strong need of changes in website construction, online forms and payments schemes. Credit union Althea is highly recommended to promote themselves by using advanced channels of communication utilized by the youth such as social media, internet forums and promo events in the Republic.